Differences Between the Prenatal Effects of Fluoxetine or Buspirone Alone or in Combination on Pain and Affective Behaviors in Prenatally Stressed Male and Female Rats - Butkevich, Irina P.; Mikhailenko, Viktor A.; Vershinina, Elena A.; Barr, Gordon A. (Frontiers in Behavioral Neuroscience, 2019)
The selective serotonin reuptake inhibitor fluoxetine and the 5-HT1A receptor agonist buspirone are used to treat depression and anxiety. Previously we demonstrated that chronic stress during pregnancy (prenatal stress) in rats, used as a model of maternal depression risk, increased inflammatory pain and depressive-like behavior in the offspring; buspirone injected to pregnant dams was protective. Clinically, the addition of buspirone to fluoxetine increases the latter’s efficacy in treating depression in patients. Here, we investigated the influence of repeated prenatal injections of fluoxetine, buspirone or their combination on pain- and depressive-like behaviors in prenatally stressed young male and female rats. Prenatal stress augmented depressive-like behavior and both thermal and inflammatory pain (formalin test), replicating our prior findings, and increased basal levels of corticosterone in the blood plasma. Both drugs and their combination reduced the effects of prenatal stress on thermal pain and depressive-like behavior independently of sex. The combination of fluoxetine and buspirone, compared with fluoxetine, was more antinociceptive in the hot plate test in both sexes, and when compared with buspirone, was more antinociceptive only in males. A detailed study of the time-course of formalin-induced pain showed a nuanced effect of these drugs that was sex-dependent. The combination of the two drugs was less effective in females than males during initial acute phase of nociceptive behavior in flexing+shaking behaviors, whereas that combination was more effective than fluoxetine alone in the first acute phase of licking behavior in females. The antinociceptive effect of buspirone dominated that of the drug combination and of fluoxetine alone, especially during the interphase of the formalin test in both sexes for both flexing+shaking and licking, suggesting a more effective prenatal action of buspirone on the development of a descending serotonergic inhibitory system modulating pain in the spinal cord dorsal horn neurons. Our results indicate that inflammatory pain-like responses integrated at the spinal level in males were more vulnerable to prenatal stress than females. In licking, the antinociceptive effect of fluoxetine and drug combination in the interphase was more in males than females. The data underscore the importance of considering of sexual dimorphism when using drug therapy.